Vegetation impacts on maximum and minimum temperatures in northeast Colorado - Hanamean, James R., Jr., author (Colorado State University. Libraries, 2001)
The impact of vegetation on the microclimate has not been adequately considered in the analysis of temperature forecasting and modeling. Vegetation has transpirational and evaporational influences in the area it inhabits, affecting the surface energy budget. The presence of vegetation, as compared to bare soil, modulates the diurnal temperature cycle. During the day, transpiring vegetation partitions a greater portion of the incoming solar energy into latent heat, decreasing the maximum temperature. At night, the vegetated area radiates energy and allows condensation, increasing the minimum temperatures via latent heat release. A daily 850-700 mb layer mean temperature, computed from the National Center for Environmental Prediction-National Center for Atmospheric Research (NCEP-NCAR) reanalysis, and satellite-derived greenness values, as defined by NDVI (Normalized Difference Vegetation Index), were correlated with surface maximum and minimum temperatures at six sites in Northeast Colorado for the years 1989-98. These sites encompass a wide array of environments, from irrigated-urban to short grass prairie. The explained variance (r-squared value) of surface maximum and minimum temperature by only the 850-700 mb layer mean temperature was subtracted from the corresponding explained variance by the 850-700 mb layer mean temperature and NDVI values. The subtraction shows that by including NDVI values in the analysis, the r-squared values, and thus the degree of explanation of the surface temperatures, increase by a mean of 6 percent for the maxima and 8 percent for the minima over the period March through October. At most sites, there is a seasonal dependence in the explained variance of the maximum temperatures because of the seasonal cycle of plant growth and senescence. Between individual sites, the highest increase in explained variance occurred at the site with the least amount of anthropogenic influence. This work suggests the vegetation state needs to be included as a factor in surface temperature forecasting, numerical modeling, and climate change assessments.
Fall 2001.
Also issued as author's thesis (M.S.) -- Colorado State University, 2001.
Keywords: Crops and climate -- Colorado; Vegetation and climate -- Colorado; Meteorology, Agricultural -- Colorado